World Wide Wait: A Study of Internet Scalability and Cache-Based Approaches to Alleviate It - Datta, Anindya; Dutta, Kaushik; Thomas, Helen; VanderMeer, Debra (Management Science, 2003)
The Internet is growing rapidly in terms of both use and infrastructure. Unfortunately, demand is outpacing the capacity of the infrastructure, as evidenced by unacceptably long response times. To support current load and further growth, we must address this problem. Several caching strategies have been proposed in the literature; many have been implemented to improve the quality of service on the Web. In this paper, we identify the main causes of delay on the Web, and provide a review of the various caching strategies employed to mitigate these delays. We also survey the application of Operations Research/Management Science (OR/MS) techniques to caching on the Web. Finally, we identify several open OR/MS research problems related to Web caching.